Effectiveness of European Green Deal: Malmquist Index Analysis on 25 EU Countries - Justyna KUJAWSKA (Communications of International Proceedings, 2025)
The aim of the article is to assess the effectiveness of the European Green Deal (EGD) implementation in EU countries. The aim was to be achieved by using the Data Envelopment Analysis (DEA) model. The additional aim is to determine which countries are most effective in achieving the Green Deal goals by analyzing the Malmquist Index. There are only few studies assessing the relative effectiveness of the EGD implementation through a comparative approach. There is a lack of studies assessing the degree of implementation of the Green Deal. There is also no development of the methods by which member states can achieve the main goal of the Green Deal, i.e. a 55% reduction in greenhouse gases by 2030. The small number of studies on the effectiveness of the implementation of the EGD goals was considered as a research gap. The research used the DEA approach to assess the effectiveness of EGD implementation in the 25 EU countries in the period of 2013–2021, using the Eurostat indicators. An outcome-oriented DEA model was developed to examine relative efficiency, and Malmquist Index were calculated, which present the change in technical efficiency and technological changes over the two the same periods in the 25 countries studied. The geometric mean of the Malmquist Index indicates an average increase of around 9% over the period studied. The results reveal significant differences in the efficiency of individual countries, with Finland, Sweden, Estonia and the Netherlands proving to be the most effective in implementing EGD, while Bulgaria, Ireland and Greece are the least effective. Countries with well-established environmental protection policies are better prepared to achieve EGD goals. Countries with a high dependence on fossil fuels, lower investment in green technologies and weaker governance structures have greater difficulties in achieving EGD goals.
Keywords: European Green Deal; DEA; effectiveness; Malmquist Index; European Union